Exposure of crumb rubber modified bitumen to UV radiation: A waste-based sunscreen for roads. (10th May 2022) - Jamal, Muhammad; Lanotte, Michele; Giustozzi, Filippo
Abstract: The degradation of asphalt roads due to heat and moisture is well studied, but very little focus has been given to the effects of high energy transmitted by sunlight UV radiations. This study aims to investigate the effect of UV radiations on the chemo-mechanical properties of neat and modified bitumen with different concentrations of crumb rubber and compare it to that of thermal ageing. Samples were aged in the Q-Lab weatherometer for 869 h at 0.89 Wm -2, equivalent to one year of UV radiations energy in the city of Melbourne, Australia, in 2019. Fourier transformation infrared (FTIR) spectroscopy was used for analysing the changes of chemical bonds before and after ageing. It was found that thermal ageing results in the development of carbonyl and sulfoxide oxides while evaporates the volatile components as depicted from the decreasing value of aliphaticity index. On the other hand, UV ageing mainly targets components with bond energy lower than 413 kJ/mol, i.e., C–C, C–O and C–H that usually consist of aliphatic chains of hydrocarbons. The rheological test results revealed that both thermal and UV ageing produce stiffer materials as depicted from the upward shift of the master curves. However, this shift reduces with the increase in CR concentration. All unaged samples were found to lay well below the Glover-Rowe onset damage envelope, however, as the samples underwent thermal ageing, they moved towards the onset damage zone. With the addition of UV ageing, the standard bitumen was only 13.2 kPa away from the 'onset damage' threshold while crumb rubber modified bitumen was almost 60 kPa away from the damage zone. Moreover, if neat bitumen is to be modified with 22.5% of CR, it can reduce the damage produced by UV and thermal ageing by approximately 50%, hence showing greater resistance to the thermal and solar radiation degradation. Highlights: UV radiations affect the durability of asphalt roads. Thermal degradation and UV ageing were analysed for crumb rubber modified bitumen. Neat binder was found to be more susceptible to UV degradation. Increasing concentration of crumb rubber reduced the impact of UV degradation.